Dekolonialisasi Sistem Kesehatan Nasional Indonesia, 1945-1960 - Uddin, Baha (Jurnal Sejarah Citra Lekha, 2025)
This article is motivated by the limited research examining the transformation of the Indonesian medical profession, especially in the early days of Indonesian independence. This is very important because the position of Indonesian doctors during that period was very important both nationally and in the development of the national health system. Therefore, the issue raised in this study is the dynamics of decolonisation of Indonesia's quality and national health system in the early days of independence. This study aims to contribute to the historical study of the decolonisation of the national health system in Indonesian historiography. The method employed is the historical method, which involves several stages of research, including heuristics, verification, interpretation, and historiography. At the beginning of independence, there was a need in the health sector to form a new identity as an independent nation. Therefore, decolonisation was carried out, covering institutions, educational institutions, the medical profession association, and the health system. This process was hampered during the independence revolution and only began in the 1950s. Indonesian doctors played a central role in this decolonisation process. They were able to transform the discriminatory, racist, and coercive colonial health system into a holistic national health system focused on improving the quality of health for the Indonesian people.